Tradisi Mapag Tuyo Pada Masyarakat Petani Di Pringsewu - Sahrozy Putra Rhomadona; Aprilia Triaristina; Risma Margaretha Sinaga; Ema Agustina (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
The mapag tuyo tradition is a Balinese tradition adapted by farmers who use Pringsewu water due to crop failures. The purpose of this study is to describe the process of implementing the Mapag Tuyo tradition in Pringsewu. This study employed qualitative methods with a descriptive approach, utilizing data collection techniques such as interviews, observation, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The Mapag Tuyo tradition in Pringsewu is adapted to local customs, including a procession of mountains of agricultural produce, a gathering of offerings, and a raid on the produce. These three stages serve to foster togetherness among farmers and serve as a form of prayer to God.